Association between variants in inflammation and cancer‐associated genes and risk and survival of cholangiocarcinoma. (15th August 2015) - Chaiteerakij, Roongruedee; Juran, Brian D.; Aboelsoud, Mohammed M.; Harmsen, William S.; Moser, Catherine D.; Giama, Nasra H.; Allotey, Loretta K.; Mettler, Teresa A.; Baichoo, Esha; Zhang, Xiaodan; Therneau, Terry M.; Lazaridis, Konstantinos N.; et al.
Abstract Genetic risk factors for cholangiocarcinoma (CCA) remain poorly understood. We assessed the effect of single‐nucleotide polymorphisms (SNPs) of genes modulating inflammation or carcinogenesis on CCA risk and survival. We conducted a case‐control, candidate gene association study of 370 CCA patients and 740 age‐, sex‐, and residential area‐matched healthy controls. Eighteen functional or putatively functional SNPs in nine genes were genotyped. The log‐additive genotype effects of SNPs on CCA risk and survival were determined using logistic regression and the log‐rank test, respectively. Initial analysis identified significant associations between SNP rs2143417 and rs689466 in cyclooxygenase 2 (COX‐2) and CCA risk, after adjusting for multiple comparisons (cutoff of P = 0.0028). However, these findings were not replicated in another independent cohort of 212 CCA cases and 424 matched controls. No significant association was found between any SNP and survival of CCA patients. Although COX‐2 has been shown to contribute to cholangiocarcinogenesis, the COX‐2 SNPs tested were not associated with risk of CCA. This study shows a lack of association between variants of genes related to inflammation and carcinogenesis and CCA risk and survival. Other factors than these genetic variants may play more important roles in CCA risk and survival.